Countering terrorism in Europe: the role of the EU - Martins, Bruno Oliveira (Politica, 2015)
Since September 2001, the European Union (EU) has developed a cross-institutional, multilevel and multifaceted approach to the fight against terrorism in parallel with efforts to build a strategic concept regarding its security identity. EU counter-terrorism encompasses instruments of different natures and the participation of several institutions and agencies, gathering a wide range of different policy areas. Over the last decade, the EU has emerged as a relevant counter-terrorism actor in Europe encompassing both internal and external instruments. EU action in countering terrorism is developed together with a legal dimension whose importance has been reinforced by the action of the Court of Justice of the European Union and the European Parliament. The article combines sociological institutionalist theory with constitutionalism to present elements for an innovative assessment of the EU as a counter-terrorism actor in Europe. It draws on policy and judicial developments from the last 14 years, and it argues that the constitutional foundations of the EU contribute decisively to the definition and mode of action of its counter-terrorism policy. This process distinguishes EU action on counter-terrorism particularly from other international counter-terrorism actors and adds new elements to assessing EU’s actorness in the broader field of security.